Coated diamond composite abrasive material and preparation process thereof
By preparing the coated diamond composite abrasive, using molybdenum metal powder to fill the tiny cracks of the diamond, and introducing aminosilane and benzene ring structures on the surface, the problems of inconsistent surface morphology and poor wetting during the grinding process are solved, and the service life and grinding performance of the abrasive tools are significantly improved.
Patent Information
- Application Number
- CN202510038105.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-10
AI Technical Summary
During the grinding process, simple free diamond abrasives have deteriorated due to inconsistent surface morphology and poor wetting properties, and diamond particles are prone to peel off.
By preparing a coated diamond composite abrasive, molybdenum metal powder and diamond powder are used for high temperature treatment to fill the tiny cracks. Then, aminosilane is introduced on the surface of the diamond particles, and a benzene ring and silane structure with extremely strong heat resistance is introduced through reaction, which is finally well compatible and combined with epoxy resin-based consolidants.
Improve the mechanical properties of diamond abrasives, reduce crushing and peeling during grinding, enhance the service life of the abrasives, and improve the bonding strength with the consolidator.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of abrasives and grinding tools, in particular to a coated diamond composite abrasive and a preparation process thereof. Background Art
[0002] Diamond, as the material with the highest known hardness, plays an important role in the abrasive tool industry. However, in some high-precision industries, such as the grinding process of silicon carbide wafers, although pure free diamond abrasives can also play a role in grinding and thinning, the free abrasives have inconsistent surface morphology, and the distribution and movement will be inconsistent during the grinding process. Therefore, when processing fine products, people often need to consolidate diamonds into grinding tools before grinding the products.
[0003] However, diamond itself has poor wettability and often cannot be firmly combined with the consolidating agent and the matrix. Diamond particles often peel off during use, resulting in a decrease in the grinding performance of the final abrasive tool. Summary of the invention
[0004] The purpose of the present invention is to provide a coated diamond composite abrasive and a preparation process thereof to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solution: a process for preparing a coated diamond composite abrasive, comprising the following steps:
[0006] S1. The diamond powder is dispersed in deionized water, heated to boiling, stirred and mixed for 30-45 minutes, filtered, and washed with anhydrous ethanol again, heated to 78-85°C and dried to constant weight, and the dried diamond powder is mixed with molybdenum metal powder, ball milled and blended for 30-45 minutes under a nitrogen atmosphere, and then mixed with sodium chloride, protected by an argon atmosphere, heated to 810-980°C, kept warm for 30-90 minutes, cooled to room temperature, and the obtained product is dispersed in deionized water, washed repeatedly to remove the sodium chloride, and the remaining product is dried to constant weight to obtain heat-treated diamond powder;
[0007] S2. The heat-treated diamond powder was dispersed in anhydrous ethanol, ultrasonically dispersed for 30-60 min, KH550 was added thereto, and after stirring and mixing, deionized water was added thereto. After stirring and reacting for 4-12 h in a dark environment, the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder.
[0008] S3. Under nitrogen atmosphere protection, dissolve pyromellitic anhydride in DMF, add p-chlorobenzenesulfonic acid thereto, continue mixing for 15-30 minutes, add amino-modified diamond powder thereto, ultrasonically disperse for 30-45 minutes, heat to 115-150°C, stir to react for 1-4 hours, centrifuge to separate the precipitate, wash the precipitate with DMF 2-3 times, and dry to constant weight to obtain anhydride-modified diamond powder;
[0009] S4. Under nitrogen atmosphere protection, tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate was dispersed in DMF, zinc chloride was added thereto, and after mixing evenly, anhydride-modified diamond powder was added. After ultrasonic dispersion for 30-45 minutes, the temperature was raised to 80-120°C, and the reaction was stirred for 4-8 hours. After centrifugal separation and precipitation, it was washed with anhydrous ethanol for 3-5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0010] Furthermore, in step S1, the particle size of the diamond powder is 1.5-30 μm; and the particle size of the molybdenum metal powder is 1.5-10 μm.
[0011] Furthermore, in step S1, the mass ratio of the diamond powder to the molybdenum metal powder and the sodium chloride is 100:(0.8-1.5):(100-150) in parts by weight.
[0012] Furthermore, in step S2, the mass ratio of the heat-treated diamond powder, anhydrous ethanol and KH550 is 1: (70-90): (8-30) in parts by weight.
[0013] Furthermore, in step S2, the mass ratio of the heat-treated diamond powder to deionized water is 1:(20-40) in parts by weight.
[0014] Furthermore, in step S3, the mass ratio of the pyromellitic anhydride, p-chlorobenzenesulfonic acid, and amino-modified diamond powder is (10-80): (0.005-0.01):1 in parts by weight.
[0015] Furthermore, in step S4, the mass ratio of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate, zinc chloride and anhydride-modified diamond powder is (5-50):(0.001-0.15):1 in parts by weight.
[0016] Furthermore, a coated diamond composite abrasive is prepared by the above method.
[0017] Furthermore, the coated diamond composite abrasive is suitable for epoxy resin-solidified diamond grinding tools.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] In order to improve the durability of diamond abrasives, the present invention performs surface modification on diamond abrasives. Since there are requirements on the particle size during the preparation of diamond abrasives, large diamond particles are often crushed during the preparation process. This process often damages the microstructure of diamonds, so that diamond particles contain a large number of tiny pores and cracks, which causes the crushing and peeling of diamond particles during the grinding process. Therefore, the present invention first uses molybdenum metal powder to treat diamond powder. Under the action of a high-temperature salt bath, the molybdenum metal powder and diamond will be infiltrated and carbonized, and in this process, the tiny cracks of the diamond will also be infiltrated and filled by the molybdenum metal, thereby improving the mechanical properties of the diamond particles and avoiding crushing during the grinding process.
[0020] On this basis, the present invention also introduces aminosilane on the surface of diamond particles by hydrolysis of KH550, and then further uses pyromellitic dianhydride containing a large number of benzene ring structures to react with amino-modified diamond powder, thereby simultaneously introducing extremely heat-resistant benzene rings and silane structures into the chain segments grafted on the diamond surface, and then reacting them again with tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate with terminal epoxy groups, so that the surface of the diamond abrasive prepared by the present invention contains a large number of epoxy groups, which can have good compatibility and bonding strength with epoxy resin-based consolidating agents, effectively improving the defect that the diamond abrasive is easy to detach after being prepared as a grinding tool, and the benzene rings and silane structures introduced in this process can also effectively reduce the phenomenon that the diamond abrasive is easy to detach due to heat generation during use of the diamond grinding tool, further enhancing the service life of the diamond grinding tool. DETAILED DESCRIPTION
[0021] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0022] The particle size of the diamond powder used in the examples and comparative examples of the present application is 5-10 μm;
[0023] Example 1. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0024] S1. Disperse 1 part of diamond powder in 100 parts of deionized water by weight, heat to boiling, stir and mix for 30 minutes, filter, wash the diamond powder again with anhydrous ethanol, heat to 85°C and dry to constant weight, mix the dried diamond powder with 0.008 parts of molybdenum metal powder, ball mill and blend for 30 minutes under nitrogen atmosphere, mix with 100 parts of sodium chloride, protect under argon atmosphere, heat to 850°C, keep warm for 60 minutes, cool to room temperature, disperse the obtained product in deionized water, wash repeatedly to remove sodium chloride, and dry the remaining product to constant weight to obtain heat-treated diamond powder;
[0025] S2. By weight, 1 part of the heat-treated diamond powder was dispersed in 80 parts of anhydrous ethanol, and after ultrasonic dispersion for 60 min, 10 parts of KH550 were added thereto, and after stirring and mixing, 20 parts of deionized water were added thereto, and the reaction was stirred in the dark for 8 h, and the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder;
[0026] S3. By weight, under nitrogen atmosphere, 10 parts of pyromellitic anhydride were dissolved in DMF, 0.01 parts of p-chlorobenzenesulfonic acid were added thereto, and the mixture was mixed for 30 minutes, and then 1 part of amino-modified diamond powder was added thereto. After ultrasonic dispersion for 45 minutes, the mixture was heated to 130°C, stirred for reaction for 2 hours, and the precipitate was separated by centrifugation. The precipitate was washed 3 times with DMF and dried to constant weight to obtain anhydride-modified diamond powder.
[0027] S4. Under nitrogen atmosphere protection, 5 parts of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate were dispersed in DMF by weight, 0.1 parts of zinc chloride were added thereto, and after mixing evenly, 1 part of anhydride-modified diamond powder was added. After ultrasonic dispersion for 45 minutes, the temperature was raised to 85°C, and the reaction was stirred for 4 hours. After centrifugal separation and precipitation, the mixture was washed with anhydrous ethanol for 5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0028] Example 2. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0029] Compared with Example 1, this embodiment increases the amount of molybdenum metal powder added in step S1;
[0030] S1. Disperse 1 part of diamond powder in 100 parts of deionized water by weight, heat to boiling, stir and mix for 30 minutes, filter, wash the diamond powder again with anhydrous ethanol, heat to 85°C and dry to constant weight, mix the dried diamond powder with 0.015 parts of molybdenum metal powder, ball mill and blend for 30 minutes under nitrogen atmosphere, mix with 100 parts of sodium chloride, protect under argon atmosphere, heat to 850°C, keep warm for 60 minutes, cool to room temperature, disperse the obtained product in deionized water, wash repeatedly to remove sodium chloride, and dry the remaining product to constant weight to obtain heat-treated diamond powder;
[0031] S2. By weight, 1 part of the heat-treated diamond powder was dispersed in 80 parts of anhydrous ethanol, and after ultrasonic dispersion for 60 min, 10 parts of KH550 were added thereto, and after stirring and mixing, 20 parts of deionized water were added thereto, and the reaction was stirred in the dark for 8 h, and the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder;
[0032] S3. By weight, under nitrogen atmosphere, 10 parts of pyromellitic anhydride were dissolved in DMF, 0.01 parts of p-chlorobenzenesulfonic acid were added thereto, and the mixture was mixed for 30 minutes, and then 1 part of amino-modified diamond powder was added thereto. After ultrasonic dispersion for 45 minutes, the mixture was heated to 130°C, stirred for reaction for 2 hours, and the precipitate was separated by centrifugation. The precipitate was washed 3 times with DMF and dried to constant weight to obtain anhydride-modified diamond powder.
[0033] S4. Under nitrogen atmosphere protection, 5 parts of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate were dispersed in DMF by weight, 0.1 parts of zinc chloride were added thereto, and after mixing evenly, 1 part of anhydride-modified diamond powder was added. After ultrasonic dispersion for 45 minutes, the temperature was raised to 85°C, and the reaction was stirred for 4 hours. After centrifugal separation and precipitation, the mixture was washed with anhydrous ethanol for 5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0034] Example 3. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0035] Compared with Example 2, this example increases the amount of KH550 added in step S2;
[0036] S1. Disperse 1 part of diamond powder in 100 parts of deionized water by weight, heat to boiling, stir and mix for 30 minutes, filter, wash the diamond powder again with anhydrous ethanol, heat to 85°C and dry to constant weight, mix the dried diamond powder with 0.015 parts of molybdenum metal powder, ball mill and blend for 30 minutes under nitrogen atmosphere, mix with 100 parts of sodium chloride, protect under argon atmosphere, heat to 850°C, keep warm for 60 minutes, cool to room temperature, disperse the obtained product in deionized water, wash repeatedly to remove sodium chloride, and dry the remaining product to constant weight to obtain heat-treated diamond powder;
[0037] S2. By weight, 1 part of the heat-treated diamond powder was dispersed in 80 parts of anhydrous ethanol, and after ultrasonic dispersion for 60 min, 30 parts of KH550 were added thereto, and after stirring and mixing, 20 parts of deionized water were added thereto, and the reaction was stirred in the dark for 8 h, and the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder;
[0038] S3. By weight, under nitrogen atmosphere, 10 parts of pyromellitic anhydride were dissolved in DMF, 0.01 parts of p-chlorobenzenesulfonic acid were added thereto, and the mixture was mixed for 30 minutes, and then 1 part of amino-modified diamond powder was added thereto. After ultrasonic dispersion for 45 minutes, the mixture was heated to 130°C, stirred for reaction for 2 hours, and the precipitate was separated by centrifugation. The precipitate was washed 3 times with DMF and dried to constant weight to obtain anhydride-modified diamond powder.
[0039] S4. Under nitrogen atmosphere protection, 5 parts of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate were dispersed in DMF by weight, 0.1 parts of zinc chloride were added thereto, and after mixing evenly, 1 part of anhydride-modified diamond powder was added. After ultrasonic dispersion for 45 minutes, the temperature was raised to 85°C, and the reaction was stirred for 4 hours. After centrifugal separation and precipitation, the mixture was washed with anhydrous ethanol for 5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0040] Example 4. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0041] Compared with Example 3, this embodiment increases the amount of pyromellitic anhydride added in step S3;
[0042] S1. Disperse 1 part of diamond powder in 100 parts of deionized water by weight, heat to boiling, stir and mix for 30 minutes, filter, wash the diamond powder again with anhydrous ethanol, heat to 85°C and dry to constant weight, mix the dried diamond powder with 0.015 parts of molybdenum metal powder, ball mill and blend for 30 minutes under nitrogen atmosphere, mix with 100 parts of sodium chloride, protect under argon atmosphere, heat to 850°C, keep warm for 60 minutes, cool to room temperature, disperse the obtained product in deionized water, wash repeatedly to remove sodium chloride, and dry the remaining product to constant weight to obtain heat-treated diamond powder;
[0043] S2. By weight, 1 part of the heat-treated diamond powder was dispersed in 80 parts of anhydrous ethanol, and after ultrasonic dispersion for 60 min, 30 parts of KH550 were added thereto, and after stirring and mixing, 20 parts of deionized water were added thereto, and the reaction was stirred in the dark for 8 h, and the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder;
[0044] S3. By weight, under nitrogen atmosphere, 80 parts of pyromellitic anhydride were dissolved in DMF, 0.01 parts of p-chlorobenzenesulfonic acid were added thereto, and the mixture was mixed for 30 minutes, and then 1 part of amino-modified diamond powder was added thereto. After ultrasonic dispersion for 45 minutes, the mixture was heated to 130°C, stirred for reaction for 2 hours, and the precipitate was separated by centrifugation. The precipitate was washed 3 times with DMF and dried to constant weight to obtain anhydride-modified diamond powder.
[0045] S4. Under nitrogen atmosphere protection, 5 parts of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate were dispersed in DMF by weight, 0.1 parts of zinc chloride were added thereto, and after mixing evenly, 1 part of anhydride-modified diamond powder was added. After ultrasonic dispersion for 45 minutes, the temperature was raised to 85°C, and the reaction was stirred for 4 hours. After centrifugal separation and precipitation, the mixture was washed with anhydrous ethanol for 5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0046] Example 5. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0047] Compared with Example 4, this example increases the amount of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate added in step S4;
[0048] S1. Disperse 1 part of diamond powder in 100 parts of deionized water by weight, heat to boiling, stir and mix for 30 minutes, filter, wash the diamond powder again with anhydrous ethanol, heat to 85°C and dry to constant weight, mix the dried diamond powder with 0.015 parts of molybdenum metal powder, ball mill and blend for 30 minutes under nitrogen atmosphere, mix with 100 parts of sodium chloride, protect under argon atmosphere, heat to 850°C, keep warm for 60 minutes, cool to room temperature, disperse the obtained product in deionized water, wash repeatedly to remove sodium chloride, and dry the remaining product to constant weight to obtain heat-treated diamond powder;
[0049] S2. By weight, 1 part of the heat-treated diamond powder was dispersed in 80 parts of anhydrous ethanol, and after ultrasonic dispersion for 60 min, 30 parts of KH550 were added thereto, and after stirring and mixing, 20 parts of deionized water were added thereto, and the reaction was stirred in the dark for 8 h, and the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder;
[0050] S3. By weight, under nitrogen atmosphere, 80 parts of pyromellitic anhydride were dissolved in DMF, 0.01 parts of p-chlorobenzenesulfonic acid were added thereto, and the mixture was mixed for 30 minutes, and then 1 part of amino-modified diamond powder was added thereto. After ultrasonic dispersion for 45 minutes, the mixture was heated to 130°C, stirred for reaction for 2 hours, and the precipitate was separated by centrifugation. The precipitate was washed 3 times with DMF and dried to constant weight to obtain anhydride-modified diamond powder.
[0051] S4. Under nitrogen atmosphere protection, 50 parts of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate were dispersed in DMF by weight, 0.1 parts of zinc chloride were added thereto, and after mixing evenly, 1 part of anhydride-modified diamond powder was added. After ultrasonic dispersion for 45 minutes, the temperature was raised to 85°C, and the reaction was stirred for 4 hours. After centrifugal separation and precipitation, the mixture was washed with anhydrous ethanol for 5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0052] Comparative Example 1. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0053] Compared with Example 1, this comparative example does not perform boiling and washing treatment on the diamond powder in step S1;
[0054] S1. Disperse 1 part of diamond powder in 100 parts of deionized water by weight, heat to boiling, stir and mix for 30 minutes, filter, wash the diamond powder again with anhydrous ethanol, heat to 85°C and dry to constant weight to obtain heat-treated diamond powder;
[0055] S2. By weight, 1 part of the heat-treated diamond powder was dispersed in 80 parts of anhydrous ethanol, and after ultrasonic dispersion for 60 min, 10 parts of KH550 were added thereto, and after stirring and mixing, 20 parts of deionized water were added thereto, and the reaction was stirred in the dark for 8 h, and the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder;
[0056] S3. By weight, under nitrogen atmosphere, 10 parts of pyromellitic anhydride were dissolved in DMF, 0.01 parts of p-chlorobenzenesulfonic acid were added thereto, and the mixture was mixed for 30 minutes, and then 1 part of amino-modified diamond powder was added thereto. After ultrasonic dispersion for 45 minutes, the mixture was heated to 130°C, stirred for reaction for 2 hours, and the precipitate was separated by centrifugation. The precipitate was washed 3 times with DMF and dried to constant weight to obtain anhydride-modified diamond powder.
[0057] S4. Under nitrogen atmosphere protection, 5 parts of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate were dispersed in DMF by weight, 0.1 parts of zinc chloride were added thereto, and after mixing evenly, 1 part of anhydride-modified diamond powder was added. After ultrasonic dispersion for 45 minutes, the temperature was raised to 85°C, and the reaction was stirred for 4 hours. After centrifugal separation and precipitation, the mixture was washed with anhydrous ethanol for 5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
[0058] Comparative Example 2. A process for preparing a coated diamond composite abrasive, comprising the following steps:
[0059] Compared with Example 1, this comparative example only carried out step S1 processing;
[0060] S1. According to the weight percentage, 1 part of diamond powder is dispersed in 100 parts of deionized water, heated to boiling, stirred and mixed for 30 minutes, filtered, and washed with anhydrous ethanol again. The diamond powder is heated to 85°C and dried to constant weight. The dried diamond powder is mixed with 0.008 parts of molybdenum metal powder, ball-milled for 30 minutes under a nitrogen atmosphere, mixed with 100 parts of sodium chloride, protected by an argon atmosphere, heated to 850°C, kept warm for 60 minutes, cooled to room temperature, and the resulting product is dispersed in deionized water. After repeated washing to remove the sodium chloride, the remaining product is dried to constant weight to obtain a coated diamond composite abrasive.
[0061] Detection: 50 parts of bisphenol AE51 epoxy resin, 28 parts of thermosetting phenolic resin 2127, and 6 g of alumina auxiliary abrasive were mixed by weight, acetone was added to adjust the viscosity of the mixed solution to 90 mPa·s, and then the mixed solution was grouped, and the coated diamond composite abrasive prepared in Examples 1-5 and Comparative Examples 1-2 was added thereto in an amount of 25 ct / mL, mixed evenly, and subjected to vacuum degassing treatment. The mixed solution was coated on a copper-plated high-carbon steel wire, and the mixture was heated to 300°C and cured for 3 hours to obtain a diamond wire saw for detection;
[0062] The diamond wire saws for detection prepared in Examples 1-5 and Comparative Examples 1-2 were respectively loaded onto an STX-402 cutting machine, and a 3-inch silicon rod was used as the detection medium. The effective cutting length of the wire saw was controlled to be 2.5 m, and the cutting speed was controlled to be 2.5 m / s. The cutting speed of the silicon rod and the diamond detachment rate when a single wire saw was broken were respectively detected. The detection results are shown in the following table;
[0063]
[0064] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a coated diamond composite abrasive, characterized in that: The following steps are involved: S1. The diamond powder is dispersed in deionized water, heated to boiling, stirred and mixed for 30-45 minutes, filtered, and washed with anhydrous ethanol again, heated to 78-85°C and dried to constant weight, and the dried diamond powder is mixed with molybdenum metal powder, ball milled and blended for 30-45 minutes under a nitrogen atmosphere, and then mixed with sodium chloride, protected by an argon atmosphere, heated to 810-980°C, kept warm for 30-90 minutes, cooled to room temperature, and the obtained product is dispersed in deionized water, washed repeatedly to remove the sodium chloride, and the remaining product is dried to constant weight to obtain heat-treated diamond powder; S2. The heat-treated diamond powder was dispersed in anhydrous ethanol, ultrasonically dispersed for 30-60 min, KH550 was added thereto, and after stirring and mixing, deionized water was added thereto. After stirring and reacting for 4-12 h in a dark environment, the precipitate was separated by centrifugation and dried to constant weight to obtain an amino-modified diamond powder. S3. Under nitrogen atmosphere protection, dissolve pyromellitic anhydride in DMF, add p-chlorobenzenesulfonic acid thereto, continue mixing for 15-30 minutes, add amino-modified diamond powder thereto, ultrasonically disperse for 30-45 minutes, heat to 115-150°C, stir to react for 1-4 hours, centrifuge to separate the precipitate, wash the precipitate with DMF 2-3 times, and dry to constant weight to obtain anhydride-modified diamond powder; S4. Under nitrogen atmosphere protection, tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate was dispersed in DMF, zinc chloride was added thereto, and after mixing evenly, anhydride-modified diamond powder was added. After ultrasonic dispersion for 30-45 minutes, the temperature was raised to 80-120°C, and the reaction was stirred for 4-8 hours. After centrifugal separation and precipitation, it was washed with anhydrous ethanol for 3-5 times, and vacuum dried to constant weight to obtain a coated diamond composite abrasive.
2. The process for preparing a coated diamond composite abrasive according to claim 1, characterized in that: In step S1, the particle size of the diamond powder is 1.5-30 μm; the particle size of the molybdenum metal powder is 1.5-10 μm.
3. The process for preparing a coated diamond composite abrasive according to claim 1, characterized in that: In step S1, the mass ratio of the diamond powder to the molybdenum metal powder and the sodium chloride is 100:(0.8-1.5):(100-150) in parts by weight.
4. The process for preparing a coated diamond composite abrasive according to claim 1, characterized in that: In step S2, the mass ratio of the heat-treated diamond powder, anhydrous ethanol and KH550 is 1: (70-90): (8-30) in parts by weight.
5. The process for preparing a coated diamond composite abrasive according to claim 1, characterized in that: In step S2, the mass ratio of the heat-treated diamond powder to deionized water is 1:(20-40) in parts by weight.
6. The process for preparing a coated diamond composite abrasive according to claim 1, characterized in that: In step S3, the mass ratio of the pyromellitic anhydride, p-chlorobenzenesulfonic acid and amino-modified diamond powder is (10-80): (0.005-0.01):1 in parts by weight.
7. The process for preparing a coated diamond composite abrasive according to claim 1, characterized in that: In step S4, the mass ratio of tri(oxiranylmethyl)benzene-1,3,5-tricarboxylate, zinc chloride and anhydride-modified diamond powder is (5-50): (0.001-0.15): 1 in parts by weight.
8. A coated diamond composite abrasive prepared by the preparation process according to any one of claims 1 to 7.
9. The coated diamond composite abrasive according to claim 8, characterized in that: The coated diamond composite abrasive is suitable for epoxy resin-solidified diamond grinding tools.
Citation Information
Patent Citations
Ultrafine-grained diamond grinding wheel and machining process thereof
CN114346919A
Diamond resin saw blade and preparation method thereof
CN114516000A
Surface modification of coated abrasives to enhance their adhesion in resin bond tools
US20030005646A1